Characterization of Black Pigment Based on Iron Oxide from Mill Scale by Simple Burning Method (Unnes Physics Journal, 2016)
Pigment is material that we use in many application such as paint, ink, material protection, and much more. There are two groups of pigment, organics pigment (dyes) that are derived from animals or plants and inorganic pigment that are derived from mineral compound. Black pigment based on iron oxide is one of inorganic pigment groups. We got iron ion (ferrous Fe2+ and ferrite Fe3+) from mill scale that we know as steel industrial's waste. Mill scale was dried under sunlight then milled to get powder form. Mill scale powders calcined on 800oC temperature in furnace and kept 2 hours so we had more homogeny and dry material with dark red-purple color. Composition of mixture solution varied from 5%, 10%, 15% and 20% weight of powder. The next process, powders was added into mixture solution of sodium hydroxide (NaOH) and ammonia hydroxide (NH4OH) so we got sludge material. Sludge burned in furnace at temperature 900oC and with 3 hours holding time so we got black material that we expect as black pigment. Black pigment samples were analyzed using XRD showed that black pigment form is hematite (Fe2O3) and the optimum color in CIELab color system are L=18.94, a=5.81, b=7.15. Commonly black pigment form is magnetite (Fe3O4), but we got it dominant in hematite form.